Coastal Zone Special Planning of an Estuary City: A Case Study of Guangzhou City, Guangdong Province - Wang Jianjun; Dai Xinzhao; Chen Shouxu; Cao Shenxi (Redai dili, 2023)
Coastal zone special planning is an important part of the territory spatial planning system in coastal cities. In the coastal zone of estuary cities, river and sea intersect, multiple spatial elements overlap, and the contradiction between development and protection is prominent. Therefore, discussing the entirety of coastal special planning for estuary cities has great theoretical and practical value. To address the technical difficulties facing the estuary city coastal zone special plan, including the delineation of the coastal zone, overall planning of the estuary and coastal space, and coordination of the planning management systems, we proposed solutions targeted to these matters in Guangzhou. (1) Method of delineating the scope of the coastal zone: We combined the delineation criteria proposed by the superior plan with the results of the shoreline revision survey to make an initial delineation of the coastal zone. Then, we connected the management units and social management boundaries along the coast of the overall territorial space plan and the specific features on the landward side to delineate the land boundary. We took all sea areas and islands in Guangzhou as the scope of the sea area study. (2) Spatial pattern construction idea of "overall structure + development unit." The overall structure is based on the "two spatial internal" red lines of the sea and ecological protection red line of the land area, the urban development boundary. The dual evaluation results and other spatial baseline schemes were used to determine the spatial scope, and the land and sea development unit was based on the integrity of the ecosystem, with development and utilization of the correlation to the comprehensive delineation. (3) Spatial control program of "multi-dimensional research and judgment + classification and control." For the nearshore sea area and coastline, two types of space were set up as control measures, respectively. At the nearshore sea area, in accordance with the development and protection of zoning to establish control objectives and response rules, the coastline was subdivided into the four types of production protection coast, production operations coast, living waterfront, and ecological protection for the implementation of the zoning classification of differentiated control measures. (4) Comprehensive management system design of "municipal coordination, planning first, and industrial access." First, the municipal government establishes a leading group for marine work. Second, the requirements of higher policies and planning are implemented and preparation for special planning for coastal zones and detailed planning for coastal areas is promoted. Third, industrial access standards implemented by zoning are established based on the retreat line of coastal buildings. Compared with other coastal cities, the preparation of special coastal zone planning of estuarine cities should pay more attention to the overall and partial hierarchical coordination, the categorical control of land and sea multiple spaces, and the oversight, guidance and constraint of cross-departmental management rules, so as to enrich the technical system of coastal zone special planning and promote the effective implementation of the land-sea integrated strategy in estuarine coastal areas.